Pemanfaatan Pupuk Organik Cair Daun Gamal dan Pengaplikasiannya terhadap Pertumbuhan Tanaman Mentimun Jepang (Cucumis Sativus L. Var. Japanese) - Nelpianni Rannu; Wartanti Wartanti; Yusuf L. Limbongan; Sepsriyanti Kannapadang; Adewidar M. Pata’dungan; Willy Yavet Tandirerung (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of organic materials as fertilizers is an important effort to improve soil fertility and crop productivity sustainably. Gliricidia sepium (gamal leaves) is a leguminous plant rich in nutrients such as nitrogen, phosphorus, and potassium, and contains bioactive compounds and microbes that support plant growth. Liquid organic fertilizer (LOF) made from fermented gamal leaves offers advantages including ease of application, high nutrient absorption by plants, and environmental friendliness compared to synthetic chemical fertilizers that may cause pollution and other negative impacts. This study aimed to evaluate the effect of LOF from gamal leaves on the growth and yield of Japanese cucumber (Cucumis sativus L.). The research was conducted at the Experimental Garden of the Faculty of Agriculture, UKI Toraja, South Sulawesi, from April to July 2025. The LOF was produced by fermenting gamal leaves for 15 days using EM-4 solution and palm sugar as activators. The LOF was applied three times at two-week intervals, starting at 7 days after planting (DAP), by soil drenching around the base of the plants. Observed variables included plant height, number of leaves, leaf area, stem diameter, number of fruits per plant and per plot, average fruit diameter and length, and fruit weight per plant and per plot. Data were analyzed using analysis of variance (ANOVA) and the Honestly Significant Difference (HSD) test at a 0.05 significance level. The results showed that application of LOF from gamal leaves at a dose of 300 ml per plant produced the best results across all observed parameters, including plant height, leaf number and area, stem diameter, fruit number, fruit size, and fruit weight per plant and per plot.